2014
DOI: 10.1039/c3lc51211h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in optofluidics-based single-cell analysis: optical on-chip cellular manipulation, treatment, and property detection

Abstract: Cellular analysis plays important roles in various biological applications, such as cell biology, drug development, and disease diagnosis. Conventional cellular analysis usually measures the average response from a whole cell group. However, bulk measurements may cause misleading interpretations due to cell heterogeneity. Another problem is that current cellular analysis may not be able to differentiate various subsets of cell populations, each exhibiting a different behavior than the others. Single-cell analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 101 publications
0
77
0
1
Order By: Relevance
“…Microfluidic chips have been used for dispensing, 19 cell analyzing, 20 and cell sorting 21 as well as drug delivery. 22,23 In 2010, Marchington et al 24 reported automated optoinjection into cells by using a microfluidic chip fabricated in polydimethylsiloxane. Propidium iodide was used for the evaluation of molecular uptake.…”
mentioning
confidence: 99%
“…Microfluidic chips have been used for dispensing, 19 cell analyzing, 20 and cell sorting 21 as well as drug delivery. 22,23 In 2010, Marchington et al 24 reported automated optoinjection into cells by using a microfluidic chip fabricated in polydimethylsiloxane. Propidium iodide was used for the evaluation of molecular uptake.…”
mentioning
confidence: 99%
“…31 Lastly, the ability to manipulate individual trapped nanoparticles may permit sorting of individual particles based on measurement characteristics, an important but underexplored area. In spite of these unique features of optical tweezers, their low throughput characteristic 32,33 presents a major challenge in its development as a multiparametric characterization tool for nanoparticles. A high-throughput capability is practically necessary to improve the efficiency of data collection when working with samples containing a low concentration of nanoparticles such as HIV virions in human blood 34 or trying to detect rare particles such as titanium oxide (TiO 2 ) in the tertiary effluent of waste water plant.…”
Section: Introductionmentioning
confidence: 99%
“…There are four main approaches to cell manipulation: optical, magnetic, electric, and mechanical. [9][10][11][12][13] Of these, the mechanical approach of hydrodynamics is usually used for applications with large numbers of cells, or cells requiring fast manipulation because it is capable of driving the whole flow in a microfluidic device. In the mechanical approach of hydrodynamics, the cell motion is usually assumed to be moving with the flow of the suspension fluid, because of its low Reynolds number.…”
Section: Introductionmentioning
confidence: 99%